A Latin Functionalist Dictionary as a Self-Learning Language Device: Previous Experiences to Digitalization - Cruz Manuel Márquez; Yuste Beatriz Chaves (MDPI AG, 2016)
The application of a methodology based on S.C. Dik's Functionalist Grammar linguistic principles, which is addressed to the teaching of Latin to secondary students, has resulted in a quantitative improvement in students' acquisition process of knowledge. To do so, we have used a self-learning tool, an ad hoc dictionary, of which the use in different practices has made students understand, at a basic level, the functioning of this language.